2015
DOI: 10.4238/2015.july.13.1
|View full text |Cite
|
Sign up to set email alerts
|

Development of expressed sequence tag-simple sequence repeat markers for Chrysanthemum morifolium and closely related species

Abstract: ABSTRACT. With the development of chrysanthemum breeding in recent years, an increasing number of wild species in genera related to Chrysanthemum were introduced to extend the genetic resources and facilitate the genetic improvement of chrysanthemums via hybridization. However, few simple sequence repeat (SSR) markers are available for marker-assisted breeding and population genetic studies of chrysanthemum and closely related species. Expressed sequence tags (ESTs) in public databases and cross-species transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
(26 reference statements)
0
7
0
1
Order By: Relevance
“…A total of 262 EST-SSR primer pairs were analysed, among which 245 primer pairs were developed from the “Jinbudiao” EST database [ 38 ] and 17 primer pairs were reported in [ 39 ]. All the SSR primer pairs were labelled with fluorescent dyes, and SSR genotyping was carried out using a three-primer strategy, including a forward/reverse primer labelled with FAM, HEX or TAMRA (Beijing Microread Genetics Co., Ltd, Beijing, China), as detailed in the protocol of Sun et al [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…A total of 262 EST-SSR primer pairs were analysed, among which 245 primer pairs were developed from the “Jinbudiao” EST database [ 38 ] and 17 primer pairs were reported in [ 39 ]. All the SSR primer pairs were labelled with fluorescent dyes, and SSR genotyping was carried out using a three-primer strategy, including a forward/reverse primer labelled with FAM, HEX or TAMRA (Beijing Microread Genetics Co., Ltd, Beijing, China), as detailed in the protocol of Sun et al [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…To validate the RNA-seq data, five differentially expressed GH18 genes at different time points (0, 3, 4, 5, and 10 days) of M. perniciosa infection of A. bisporus were analyzed by PCR and RT-PCR. Specific primers (Table 1) were designed for the five GH18 genes using Primer Premier 5.0 software (Liu et al, 2015). Approximately 200 ng/µL of DNA and cDNA products were used as templates for the PCR and RT-PCR.…”
Section: Gene Cloning and Analysis Of The Gh18 Genesmentioning
confidence: 99%
“…SSRs are frequently used to survey phylogenetic relationships and select loci associated with agronomic traits in D. morifolium cultivars (Chen et al, 2016). Previous studies have reported some D. morifolium SSR markers (Moe et al, 2011;Khaing et al, 2013;Liu et al, 2015;Shim et al, 2015). However, the limited number of SSR markers available for D. morifolium fails to meet the requirements for genetic diversity evaluation, as well as linkage and association analyses.…”
Section: Introductionmentioning
confidence: 99%